Evaluation of the Results of Left Bundle Branch Pacing after Atrioventricular Junction Ablation in Patients with Chronic Atrial Fibrillation - Perepeka, Eugene O.; Kravchuk, Borys B. (Ukrainian Journal of Cardiovascular Surgery, 2024)
Atrioventricular junction ablation (AVJA) together with the implantation of cardiac pacemaker has become a recognized and effective treatment strategy for patients with symptomatic tachysystolic atrial fibrillation that does not respond to heart rate control drug therapy. Left bundle branch pacing (LBBP) is a physiological alternative to right ventricular and biventricular pacing. The aim. To analyze the clinical results of the average duration with the use of LBBP and AVJA. Materials and methods. Over the period from January 2023 to July 2024, LBBP with subsequent AVJA was applied at the National Amosov Institute of Cardiovascular Surgery in 18 patients as a method of treatment of chronic tachysystolic atrial fibrillation to achieve heart rate control. Results. Mid-term results (at least 1 month) could be monitored in 15 out of 18 patients (84%); in the other three (16%) patients the time between pacemaker implantation and AVJA was too short. The mean period from pacemaker implantation to control examination was 5.07 ± 2.79 months (minimum period 1 month, maximum 12 months). During the period from implantation and ablation to the control observation in the study group, it was possible to observe an increase in left ventricular ejection fraction from 39.12 ± 10.56% to 46.38 ± 7.09%, p = 0.035; decrease in the values of end-diastolic volume from 184.22 ± 76.76 to 167.85 ± 36.93 ml, p = 0.074; decrease in the right ventricular pressure from 43.07 ± 8.29 to 34.38 ± 4.78 mm Hg, p = 0.013. It was also possible to observe a decrease in the left bundle branch capture thresholds from 1.27 ± 0.58 to 0.7 ± 0.39 V at 0.4 ms, p = 0.016; and a decrease in the average LBBP endocardial lead resistance from 638 ± 172.83 to 529.4 ± 120.15 Ohm, p = 0.012. Conclusions. Implantation of the LBBP pacemaker and AVJA was not associated with the occurrence of complications both in the intraoperative and postoperative periods, as well as in the remote period of the average duration in the studied group. The use of this approach in patients with chronic atrial fibrillation made it possible in a series of consecutive patients to improve the systolic function of the left ventricle, to reduce the values of the end-diastolic volume of the left ventricle and the right ventricular pressure at optimal pacing parameters.